2020
DOI: 10.1002/etc.4887
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of Ecotoxicological Hazard Data for Nanoplastics in Marine and Freshwater Systems

Abstract: There is emerging concern about the potential health and environmental impacts of nanoplastics in the environment. Information on exposure has been lacking, but a growing amount of ecotoxicological hazard data is now available, allowing a hazard assessment to be conducted for nanoplastics in freshwater and marine systems. Based on a critical evaluation of published studies and the construction of probabilistic species sensitivity distributions (PSSDs), we present a comprehensive, state-of-the-art understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…For chemicals, on average, such systematic differences in effect concentrations between freshwater and saltwater species were not observed (see de Zwart, 2002; Wheeler et al, 2002, 2014). According to a previous study that derived SSDs for nanoplastics (Yang & Nowack, 2020), the HC5 value estimated based on the full data set obtained in marine media (1.3 μg/L) was lower than that obtained in freshwater media (71 μg/L), but values were comparable after removing data measured in the presence of NaN 3 . It is not possible to identify the underlying reasons because of the limited availability of data.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…For chemicals, on average, such systematic differences in effect concentrations between freshwater and saltwater species were not observed (see de Zwart, 2002; Wheeler et al, 2002, 2014). According to a previous study that derived SSDs for nanoplastics (Yang & Nowack, 2020), the HC5 value estimated based on the full data set obtained in marine media (1.3 μg/L) was lower than that obtained in freshwater media (71 μg/L), but values were comparable after removing data measured in the presence of NaN 3 . It is not possible to identify the underlying reasons because of the limited availability of data.…”
Section: Resultsmentioning
confidence: 86%
“…We incorporated the reference‐level random effects (parameter r ) in the HSSD modeling to describe the variations in effect concentrations due to reference‐specific unmodeled factors. These unmodeled factors include differences in physicochemical conditions (e.g., the presence or absence of NMP particle preprocessing including removal of sodium azide stabilizer (Besseling et al, 2019; Yang & Nowack, 2020) and biological conditions (e.g., developmental stage and origin of organisms) in tests. Without incorporating random effects in the estimation of HC5, the posterior medians of HC5 were 166.0 and 17.6 μg/L for plastic particles with a size of 0.1 μm in freshwater and marine environments, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When including HONEC (Highest Observed No Effect Concentration) values, there was a trend that particles larger than 100 µm had a larger NOEC, i.e., were less toxic. A meta-analysis of nanoplastics ecotoxicity data [55] revealed that the nanoplastic predicted no-effect concentration (PNEC) was much larger than the microplastics PNEC, suggesting that smaller plastic particles are not necessarily more toxic as often suggested. Hence, the use of one effect factor for all sizes of microplastics is, therefore, a suitable approach given the current state of knowledge.…”
Section: Discussionmentioning
confidence: 96%